Levantamento florístico de Bryopsida de cerrado e mata ripícola do Parque Nacional de Sete Cidades, Piauí, Brasil Bryopsida from the cerrado and gallery forest of the Sete Cidades National Park, in the State of Piauí, Brazil - Nívea Maria Carneiro Farias Castro (Acta Botânica Brasílica, 2002)
Foi realizado o levantamento florístico das Bryopsida dos ecossistemas de cerrado e de mata ripícola do Parque Nacional de Sete Cidades localizado nos municípios de Piracuruca e Brasileira (04º0515'S e 41º3045'W), Piauí, Brasil. Foram identificadas 22 espécies de musgos pertencentes às famílias: Bartramiaceae (1 sp.), Bryaceae (2 sp.), Calymperaceae (2 sp.), Dicranaceae (3 sp.), Erpodiaceae (1 sp.), Fissidentaceae (6 sp.), Hypnaceae (1 esp.), Leucobryaceae (1 sp.), Pottiaceae (2 sp.), Sematophyllaceae (2 sp.) e Stereophyllaceae (1 sp.). Constituem-se novas referências para o Brasil, Weisiopsis nigeriana (Egun. & Olar.) Zand.; para o Nordeste, Campylopus heterostachys (Hampe) Jaeg. e para o Estado do Piauí: Bryum capillare Hedw., Bryum cruegeri Hampe ex C.Müller, Philonotis uncinata (Schwaegr.) Brid., Vesicularia vesicularis (Schwaegr.) Broth., Sematophyllum subsimplex (Hedw.) Mitt., Trichosteleum fluviale (Mitt.) Jaeg., Hyophila involuta (Hook.) Jaeg. & Sauerb., Calymperes palisotii Schwaegr. ssp. richardii (C.Müller) S.Edwards, Fissidens guianensis Mont., Fissidens intermedius C.Müller, Fissidens prionodesMont., Fissidens goyazensis Broth. eFissidens zollingeri Mont. Aos táxons são indicadas referências de descrições, ilustração e distribuição geográfica. This study is a floristic survey of the Bryopsida from the "cerrado" and from the gallery forest of the Sete Cidades National Park in the municipalities Piracuruca and Brasileira, in the State of Piauí, Brazil (04º0515'S and 41º30-45'W). Twenty-two taxa were determined from the following families: Bartramiaceae (1 esp.), Bryaceae (2 esp.), Calymperaceae (2 esp.), Dicranaceae (3 esp.), Erpodiaceae (1 esp.), Fissidentaceae (6 esp.), Hypnaceae (1 esp.), Leucobryaceae (1 esp.), Pottiaceae (2 esp.), Sematophyllaceae (2 esp.) and Stereophyllaceae (1 esp.). Weisiopsis nigeriana (Egun. & Olar.) Zand. is the first record of this species to Brazil, Campylopus heterostachys (Hampe) Jaeg. is the first of this species found in Brazilian northeast, and Bryum capillare Hewd., Bryum cruegeri Hampe ex C.Müller, Philonotis uncinata (Schwaegr.) Brid., Vesicularia vesicularis (Schwaegr.) Broth., Sematophyllum subsimplex (Hedw.) Mitt., Trichosteleum fluviale (Mitt.) Jaeg., Hyophila involuta (Hook.) Jaeg. & Sauerb., Calymperes palisotii Schwaegr. ssp. richardii (C.Müller) S.Edwards, Fissidens guianensis Mont., Fissidens intermedius C.Müller, Fissidens prionodes Mont., Fissidens goyazensis Broth. and Fissidens zollingeri Mont. are new to the State of Piauí. For each taxon a description is given along with references, illustrations and geographical distribution.